Quan hệ giữa quy luật phân mùa dòng chảy các tai biến tự nhiên tại dải Duyên hải Miền Trung - Dân, Nguyễn Lập; Lan, Vũ Thu (Vietnam Journal of Earth Sciences, 2004)
The relationship between the rule of dividing flow seasons and natural catastrophes in the Central Coastal zone